Good conduct makes your face attractive: The effect of personality perception on facial attractiveness judgments - Niimi, Ryosuke; Goto, Mami (PLOS ONE, 2023)
Human facial attractiveness is related to physical features, such as clear complexion and symmetry. However, it is also known that facial attractiveness judgments are influenced by a wide range of non-physical factors. Here, we examined the effect of the personality information of a target person on facial attractiveness judgments. In Experiment 1, participants read a verbal description of a target person (high or low honesty), followed by the presentation of the target face and facial attractiveness rating. The honest personality increased the rated facial attractiveness, replicating a previous report. This “honesty premium” effect was independent of pre-rated facial attractiveness (Experiment 1), target gender, participant gender, and target clothing (Experiment 2). Experiment 3 found that creative personality did not affect facial attractiveness ratings, while an aggressive personality was suggested to decrease the rated facial attractiveness of male targets. We did not find evidence that participants’ moods caused these effects. The results suggest that the “what is good is beautiful” stereotype is robust and that facial attractiveness is malleable and dependent on various physical and non-physical information.